Determinan Tingkat Kemiskinan di Wilayah Pesisir Utara Jawa Timur - Anggraini, Vidya; Viphindrartin, Sebastiana; Santoso, Edy; Purtomo Somaji, Rafael; Istiyani, Nanik (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2023)
The main problem of economic development is poverty and the main goal of national development is to eradicate poverty. The purpose of this study is to see the effect of Economic Growth, Human Development Index, and the Open Unemployment Rate on the Poverty Level in the northern coastal region of East Java. This study uses panel data, which combines time series and cross section data for 5 years, from 2016 to 2020. The results of the study show that the best model for estimating poverty levels in the northern coastal region of East Java is the random effect model. The results showed that Economic Growth had a negative and significant effect on the Poverty Level. The Human Development Index (HDI) has a negative and significant effect on the Poverty Level. The Open Unemployment Rate has a negative and significant effect on the Poverty Level.